2020
DOI: 10.1111/bcp.14646
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ABCB1 and CES1 polymorphisms on dabigatran pharmacokinetics and pharmacodynamics in patients with atrial fibrillation

Abstract: Our study aimed to determine the impact of genetic polymorphisms of ABCB1 and CES1 on the pharmacokinetics (PK) and pharmacodynamics (PD) of dabigatran in patients with nonvalvular atrial fibrillation (NVAF). Methods:We conducted a prospective study and enrolled NVAF patients treated with dabigatran. Blood samples were obtained from each patient and used for genotyping and determination of plasma dabigatran concentration (PDC) and coagulation parameters including activated partial thromboplastin time (APTT) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
32
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 24 publications
7
32
1
1
Order By: Relevance
“…Our results on the ABCG2 c.421C>A SNV are in line with the results of earlier prospective studies on plasma concentration and drug clearance 11,15,40 as well as with a case report 41 . Our results on CES1 c.257+885T>C SNV are in line with studies reporting association of the variant with drug plasma concentration 13,16,42 …”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results on the ABCG2 c.421C>A SNV are in line with the results of earlier prospective studies on plasma concentration and drug clearance 11,15,40 as well as with a case report 41 . Our results on CES1 c.257+885T>C SNV are in line with studies reporting association of the variant with drug plasma concentration 13,16,42 …”
Section: Discussionsupporting
confidence: 91%
“…41 Our results on CES1 c.257+885T>C SNV are in line with studies reporting association of the variant with drug plasma concentration. 13,16,42 The present study revealed once again the important role of antiplatelets as interacting drugs. Antiplatelets are in many cases used in parallel with a DOAC to increase protection towards thromboembolic events.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In addition, the genotype frequency of Chinese in our study is very similar to that of Chinese in other study. 19 In the present study the Cmax and AUC 0-∞ of total dabigatran were approximately 20% higher than that in Caucasians. Allele C of CES1 rs2244613 was associated with decreased dabigatran trough concentration and decreased risk of bleeding, but not to the peak concentration.…”
Section: Discussioncontrasting
confidence: 45%